Hepatocellular carcinoma. Multimodal treatment (2008)
Hepatocellular Carcinoma (HCC) continues to grow as a disease of the Western hemisphere. Various treatment options exist for HCC. In this article we review the currently available options. © 2008 Asociaciones Colombianas de Gastroenterología, Endoscopia digestiva, Coloproctología y Hepatología.